Network security : (Wiley, 2007)
Network Security provides the latest research and addresses likely future developments in network security protocols, architectures, policy, and implementations. It covers a wide range of topics dealing with network security, including secure routing, designing firewalls, mobile agent security, Bluetooth security, wireless sensor networks, securing digital content, and much more.